Penerapan Pendekatan Lingkungan dalam Meningkatkan Pemahaman Materi IPA di SDN Suryakencana CBM - Sobur, Abdul (utile: Jurnal Kependidikan, 2018)
This classroom action research based on students score average of science arenot able to reach 67 as a minimum score in class. Unoptimal learning model as one ofmany indicators of the students score problem. The aim of the research are; 1) to observelearning implementation plan; 2) to observe student learning activities in class; 3) toobserve implementation of environment approach as learning model in science and itinfluences to 6th grade students score in Suryakencana CBM Elementary School. Themethod of rhe research is Classroom Action Research through three cycles of learning.The research subjects are 29 students of 6th grade. The research conludes of 1st cycle thatis students score average just reach 60.43. On 2nd cycle has rised to 71.74, then on 3rdcycle has rised significantly to 83.48. According to the score average result, environtmentapproach of learning is able to rise the students score of science optimally.